Optimization of substation grounding grid design for horizontal and vertical multilayer and uniform soil condition using Simulated Annealing method - Permal N.; Osman M.; Ariffin A.M.; Boopalan N.; Abidin Ab Kadir M.Z. (Public Library of Science, 2023)
algorithm; Article; cost; electric resistance; electricity; engineering; grounding grid system; process optimization; safety; simulated annealing; soil property; soil structure; chemistry; computer simulation; electric conductivity; electric power plant; impedance; soil; spatial analysis; theoretical model; Algorithms; Computer Simulation; Electric Conductivity; Electric Impedance; Models, Theoretical; Power Plants; Soil; Spatial Analysis